2019
DOI: 10.1111/jbi.13700
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the geographic and climatic origins of long‐distance bird migrations

Abstract: Aim Seasonal bird migration is one of the most fascinating global ecological phenomena. Yet, the biogeographic scenarios and climatic drivers that led single species or entire lineages to evolve seasonal migration between disjunct breeding and wintering ranges remain unclear. Based on distribution and phylogenetic data for all birds worldwide, we explored the biogeographic and climatic context of the evolutionary emergence of seasonal geographic migration in birds. Location Global. Taxon The Aves class (9,819 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 55 publications
(124 reference statements)
7
78
2
Order By: Relevance
“…3 (continued) 2013) and in Turdus (Nagy et al 2019). This pattern is congruent with the findings of a study that examined a broader set of taxa, in which migratory lineages appeared earlier during the evolution of the Passeriformes (Dufour et al 2020). Similarly to raptors, speciation and rapid radiation also started in Turdidae during the Miocene (Nagy et al 2019;Nagy 2019).…”
Section: The Evolution Of Migration In Accipitriformes and In Turdidaesupporting
confidence: 72%
See 2 more Smart Citations
“…3 (continued) 2013) and in Turdus (Nagy et al 2019). This pattern is congruent with the findings of a study that examined a broader set of taxa, in which migratory lineages appeared earlier during the evolution of the Passeriformes (Dufour et al 2020). Similarly to raptors, speciation and rapid radiation also started in Turdidae during the Miocene (Nagy et al 2019;Nagy 2019).…”
Section: The Evolution Of Migration In Accipitriformes and In Turdidaesupporting
confidence: 72%
“…boreal, mountainous, arid, tropical) migration is more likely to have evolved early (e.g. Dufour et al 2020). Consequently, the ancestral migratory behaviour established the flexibility for other behavioural changes such as in foraging strategies.…”
Section: Major Biogeographic Events and Climatic Conditions During Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors may explain the lack of response of avian predation to latitudinal or climatic gradients. First, bird species are distributed through migration allowing them to breed at higher latitudes, resulting in a constant predation rate across climatic and geographical clines (Dufour et al, 2020). In contrast, other predators with lower mobility such as arthropods (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zurell et al (2018) found that migratory birds track green vegetation (measured by NDVI) to a greater degree than climatic conditions. In contrast, Dufour et al (2020) found no evidence of niche tracking when examining the temperature niche.…”
Section: Discussionmentioning
confidence: 79%